White Paper: Bridging the gap between surveillance data and antimicrobial stewardship in the animal sector—practical guidance from the JPIAMR ARCH and COMBACTE-MAGNET EPI-Net networks. (6th December 2020) - Compri, Monica; Mader, Rodolphe; Mazzolini, Elena; de Angelis, Giulia; Mutters, Nico T; Babu Rajendran, Nithya; Galia, Liliana; Tacconelli, Evelina; Schrijver, Remco; ,
Abstract: Background: The JPIAMR ARCH and COMBACTE-MAGNET EPI-Net networks have joined efforts to formulate a set of target actions to link the surveillance of antimicrobial usage (AMU) and antimicrobial resistance (AMR) with antimicrobial stewardship (AMS) activities in four different settings. This White Paper focuses on the veterinary setting and embraces the One Health approach. Methods: A review of the literature was carried out addressing research questions in three areas: AMS leadership and accountability; AMU surveillance and AMS; and AMR surveillance and AMS. Consensus on target actions was reached through a RAND-modified Delphi process involving over 40 experts in infectious diseases, clinical microbiology, AMS, veterinary medicine and public health, from 18 countries. Results/discussion: Forty-six target actions were developed and qualified as essential or desirable. Essential actions included the setup of AMS teams in all veterinary settings, building government-supported AMS programmes and following specific requirements on the production, collection and communication of AMU and AMR data. Activities of AMS teams should be tailored to the local situation and capacities, and be linked to local or national surveillance systems and infection control programmes. Several research priorities were also identified, such as the need to develop more clinical breakpoints in veterinary medicine. Conclusions: This White Paper offers a practical tool to veterinary practitioners and policy makers to improve AMS in the One Health approach, thanks to surveillance data generated in the veterinary setting. This work may also be useful to medical doctors wishing to better understand the specificities of the veterinary setting and facilitate cross-sectoral collaborations.